Nanostructured Samarium Doped Fluorapatites and Their Catalytic Activity towards Synthesis of 1,2,4-Triazoles - Kranthi Kumar Gangu; Suresh Maddila; Surya Narayana Maddila; Sreekantha B. Jonnalagadda (Molecules, 2016)
An investigation was conducted into the influence of the amino acids as organic modifiers in the facile synthesis of metal incorporated fluorapatites (FAp) and their properties. The nanostructured Sm doped fluorapatites (Sm-FAp) were prepared by a co-precipitation method using four different amino acids, namely glutamic acid, aspartic acid, glycine and histidine. The materials were characterized by various techniques including X-ray diffraction (XRD), Fourier transform infra-red spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), high resolution transmission electron microscopy (HR-TEM), N2-adsorption/desorption isotherm, temperature programmed desorption (TPD) and fluorescence spectrophotometry. Under similar conditions, Sm-FAp prepared using different amino acids exhibited distinctly different morphological structures, surface area and pore properties. Their activity as catalysts was assessed and Sm-FAp/Glycine displayed excellent efficiency in the synthesis of 1,2,4-triazole catalyzing the reaction between 2-nitrobenzaldehyde and thiosemicarbazide with exceptional selectivity and 98% yield in a short time interval (10 min). The study provides an insight into the role of organic modifiers as controllers of nucleation, growth and aggregation which significantly influence the nature and activity of the catalytic sites on Sm-FAp. Sm-FAp could also have potential as photoactive material.